Life Cycle Assessment of the Campus Wastewater Treatment Using the Lab-scale of Anaerobic Baffled Reactor - Aziz, Hafif Ahmad Abdul; Yulistyorini, Anie; Rifai, Ridwan Muhamad; Hamzah, Sofiah (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
In Indonesia, the waste sector is responsible for 10.59% (130,188.21 GgCO2e) of global warming emissions, one of which is from campus domestic wastewater due to the lack of wastewater treatment plants. Only 0.2% of the 6,472 campuses have treatment systems, such as Universitas Negeri Malang (UM) use a fabricated anaerobic baffled reactor (FABR) for wastewater treatment plants for its green campus initiatives, yet available only for several buildings and do not treat all wastewater generated from the campus activity. However, Life Cycle Assessment (LCA) of ABR system has not been widely studied, especially when it uses in treating of the campus wastewater. This study aims to conduct the LCA of the laboratory -scale ABR system in the campus wastewater treatment with gate-to-gate scope using Simapro 9.1.11 and the CML-IA Baseline. Three scenarios were tested: untreated wastewater, ABR equipped with peristaltic pumps, ABR without pumps. The results indicated that ABR treatment had a significantly lower environmental impact than untreated wastewater, with the greatest reduction in global warming potential (1.51E-08 to 4.98E-11), followed by eutrophication and photochemical oxidation. This study is limited to the ABR system, future research could expand to include the full lifecycle, from material collection to final results.